2017
DOI: 10.1002/jso.24495
|View full text |Cite
|
Sign up to set email alerts
|

De novo thyroid cancer following solid organ transplantation—A 25‐year experience at a high‐volume institution with a review of the literature

Abstract: Rate of thyroid cancer is not significantly higher in patients who underwent solid organ transplantation compared to general population. Stage at presentation and prognosis also appear to be similar to that of the general population. Post-transplant screening for thyroid cancer remains debatable; however, when thyroid cancer is discovered, treatment should be similar to that of non-transplant patients. J. Surg. Oncol. 2017;115:105-108. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…Salivary gland tumors have previously been linked to history of transplant, so our findings agree with prior research . Thyroid cancers have also previously been shown to be increased in transplant patients . Interestingly, though immunosuppression has been hypothesized to be the driver of most cancer formation in transplant recipients (particularly virus‐associated cancers, as previously discussed), thyroid cancers may not follow this pattern .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Salivary gland tumors have previously been linked to history of transplant, so our findings agree with prior research . Thyroid cancers have also previously been shown to be increased in transplant patients . Interestingly, though immunosuppression has been hypothesized to be the driver of most cancer formation in transplant recipients (particularly virus‐associated cancers, as previously discussed), thyroid cancers may not follow this pattern .…”
Section: Discussionsupporting
confidence: 90%
“…One recent large study of thyroid risk found an SIR of 2.5, and noted that the high rate of thyroid cancers may be partially due to surveillance bias; however, the same study found an increased rate of larger and higher stage thyroid cancers, which are less likely than smaller, low stage tumors to be affected by surveillance bias . Additionally, prior estimates of thyroid cancer risk in transplant recipients have been wide‐ranging, which may be because thyroid cancer rates have increased in the general population over time, making comparisons between longitudinal cohorts and population risk estimates more problematic . Thus, our estimation of an RR of 1.9 for thyroid cancer in transplant patients may be more accurate than prior estimates that suggested SIRs of as high as 6.9 or 7.0 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Even if transplant recipients were to develop de novo papillary thyroid cancer, their risk of death would be much greater from end‐stage renal disease (approximately a 60% 5‐year survival on dialysis) than from papillary thyroid cancer. Unlike many other cancers, papillary thyroid cancer does not appear to progress more rapidly post‐transplant, nor does it occur at a more advanced stage . Direct metastasis to the transplanted kidney from solid malignancies is exceedingly rare …”
Section: Transmission Riskmentioning
confidence: 99%
“…Kouter and Duh from UCSF have reviewed their experience of thyroid cancer, occurrence, stage, management and prognosis in individuals who have undergone solid organ transplantation at their institution . Clearly, they have a large series of patients having undergone solid organ transplant surgery including kidney, liver, and pancreas.…”
mentioning
confidence: 99%